Shipping Cattle, Not Tropical Soda Apple Seed - Jeff Mullahey; Pat Hogue (EDIS)
This document is WEC 176, one of a series of the Wildlife Ecology and Conservation Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: May, 2003.